PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ISPRING SUITE 9 PADA MATA PELAJARAN DASAR LISTRIK DAN ELEKTRONIKA KELAS X TITL DI SMK - Pinka Kezia; Hamonangan Tambunan (JEVTE Journal of Electrical Vocational Teacher Education, 2023)
Abstract The problem in this study is the lack of explanation of material in the form of animation, the use of technology in conveying information so that students do not understand and are interested in the material presented. Many students already have smartphones but only a small percentage use them for learning. Delivery of material in the form of textbooks, whiteboards and markers. The objectives of this study are (1) to determine the design process of developing Ispiring Suite 9 learning media in basic electrical and electronics subjects class X TITL, (2) to determine the feasibility of learning media designed so that this learning media is valid and can be used by students. The research model used in this study from Thiagarajan consists of define, design, development, and dissemination (4D). The subjects of this study were class X TITL2 students of SMKN 14 Medan, while the media assessment validators were UNIMED lecturers and homeroom teachers X TITL2 to assess the material and media. The results of this study show that interactive learning media based on Ispiring Suite 9 is classified as "Excellent". Based on the results of the assessment the validator got the category "Very Worthy" with details from the media expert validator got a percentage score of 93.2% with the category "Very Decent". On the assessment of the media by material experts obtained a percentage score of 94% with the category "Very Decent". Based on the four validators, it can be concluded that interactive learning media based on Ispiring Suite 9 is suitable for use for class X TITL students of SMKN 14 Medan. Â Key Words: Media Ispiring Suite 9, Passive and Active Components, Electrical Energy PowerÂ AbstrakPermasalahan dalam penelitian ini adalah kurangnya penjelasan materi berupa animasi, pemanfaatan teknologi dalam menyampaikan informasi sehingga siswa kurang memahami dan tertarik pada materi yang disajikan. Banyak siswa yang sudah memiliki smartphone namun hanya sebagian kecil yang menggunakannya untuk pembelajaran. Penyampaian materi berupa buku pelajaran, papan tulis dan spidol. Tujuan penelitian ini adalah (1) untuk mengetahui proses rancangan pengembangan media pembelajaran Ispiring Suite 9 pada mata pelajaran Dasar Listrik dan Elektronika kelas X TITL, (2) untuk mengetahui kelayakan media pembelajaran yang dirancang agar media pembelajaran ini valid dan dapat digunakan oleh siswa. Adapun model penelitian yang digunakan dalam penelitian ini dari Thiagarajan terdiri dari define, design, development, dan dissemination (4D). Subjek penelitian ini adalah siswa kelas X TITL2 SMKN 14 Medan, sedangkan validator penilaian media yaitu dosen UNIMED dan guru wali kelas X TITL2 untuk menilai materi dan media. Hasil penelitian ini menunjukkan bahwa media pembelajaran interaktif berbasis Ispiring Suite 9 tergolong pada kategori â€œSangat Baikâ€. Berdasarkan hasil dari penilaian validator mendapat kategori â€œSangat Layakâ€ dengan rincian dari validator ahli media mendapat skor persentase 93,2% dengan kategori â€œSangat Layakâ€. Pada penilaian media oleh ahli materi diperoleh skor persentase 94% dengan kategori â€œSangat Layakâ€. Berdasarkan dari keempat validator dapat disimpulkan bahwa media pembelajaran interaktif berbasis Ispiring Suite 9 layak digunakan untuk siswa kelas X TITL SMKN 14 Medan..Â Kata Kunci: Media Ispiring Suite 9, Komponen Pasif &Aktif, Daya Energy Listrik